Effects of the Hydroxy-Regulated Li-Montmorillonite Atomic Interface Arrangement on Li Cycle of Marine Sedimentation and pH - Yan, Song (Langmuir : the ACS journal of surfaces and colloids, 2024)
The reaction of ubiquitous clay is related to the global cycle of the key metals, but the relationship between the Li occurrence interface and the sedimentation in the Li cycle remains unclear. We investigated the atomic interface arrangement of Li-montmorillonite (Li-Mt) during low-temperature water-rock reactions and Li migration. The results show that, in Cl-rich systems, deprotonation and exposure of Na adsorption sites cause Li enrichment and O pairing, which lead to the weakening of the shielding effect of Mt on anions and the formation of a Mt-Li-Cl atomically interfacial arrangement. Only up to 20.3% of the Li is contained in the atomic interface of Li-Mt. In F-rich system, the dehydroxylation of F paired with Al in octahedral sites causes Li accumulation via local crystallization of LiF, and co-complexation of F and Li forms a Mt(Al)-F-Li atomic interface, in which up to 46.8% of the Li is enriched by the Mt. The participation of F and Cl in the complexation intensifies lattice collapse of the Li-Mt edge. The sedimentation velocity decreases with the smaller particle size affected by the Li loading. Lithium leached from igneous rocks serves as the marine Li source, which contributes up to 99.8% and 99.5% of the Li in Cl- and F-rich systems, respectively. The response of Mt(OH) to Li migration with a time accumulating effect may make an important regulatory of oceanic pH by either acidification or alkalization